Improvement of Mechanical Characteristics on Ultra-High Molecular Weight Polyethylene Surface through Zinc Oxide Atomic Layer Deposition Film - Minpyo Hong; Kyungmin Kim; Yongnam Song (Advances in Materials Science and Engineering)
Wear failures in ultra-high molecular weight polyethylene (UHMWPE) compartments are known to limit the life of a joint implant. In this study, we applied atomic layer deposition (ALD) technique to produce wear-resistant zinc oxide (ZnO) films to improve mechanical and wear characteristics on the surface of UHMWPE. Organic material layers in molecular units were mixed with ALD ZnO films to minimize surface cracks through a molecular layer deposition (MLD) technique. We aimed to examine (1) the effect of organic layers on minimizing surface cracks and (2) the mechanical properties of ZnO and inorganic/organic hybrid films. We prepared UHMWPE samples with pure ZnO and five different hybrid films with ZnO to organic layer ratios of 1 : 1, 2 : 1, 3 : 1, 4 : 1, and 5 : 1. Surface cracks were observed by using a field-emission scanning electron microscope. Hardness and elastic modulus of an ALD-coated UHMWPE were measured by nano-indentation examinations. Severe cracks were found in the samples with pure ZnO films. However, no cracks were found in the samples with all hybrid films except the samples with a ZnO to organic layer ratio of 5 : 1. The hardness and elastic modulus of the samples with pure ZnO and hybrid films significantly increased compared to those of the native UHMWPE. The hardness to elastic modulus ratios, indicating the wear resistance, increased over 50% for all films compared to the values of native UHMWPE. These results suggested that ALD ceramic coatings with organic layers may become a potential solution for realizing a wear-resistant protection coating for the polymer compartment of joint prostheses.